(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the importance of developing the creative abilities of students based on interactive teaching methods and technologies. Works of a number of scientists about creativity. Opinions are presented on the assessment and development of practical skills and creative abilities of students using international experience.